Amigos and Amistades: The role of men’s social network ties in shaping HIV vulnerability in the Dominican Republic - Fleming, Paul J. (2014)
While men’s social networks have been identified as a source of influence on sexual behaviour, less is known about the different types of friendship ties within men’s networks. We analysed data from qualitative in-depth interviews with 36 men in Santo Domingo, Dominican Republic who were current or former sexual partners of female sex workers to understand how a) men describe trust and communication with different types of friendship ties, b) characteristics of trust and communication reflect norms of masculinity, and c) these friendship ties influence HIV-related behaviours. We identified a distinction between amistades, social drinking buddies who are not trusted, and amigos, trusted friends. The majority of men lacked any amigos and some had neither amigos nor amistades. In general, men reflected traditional norms of masculinity and said they did not feel they could discuss their relationships or emotional topics with other men. Trust and communication dynamics, and how norms of masculinity shape those dynamics, should be understood and addressed in the design of HIV prevention efforts with men’s social networks as they have implications for the potential effectiveness of such efforts.